2011
DOI: 10.1111/j.1601-183x.2011.00689.x
|View full text |Cite
|
Sign up to set email alerts
|

ACHRNA5allele related to nicotine addiction and schizophrenia

Abstract: Schizophrenia and nicotine addiction are both highly heritable phenotypes. Because individuals with schizophrenia have a higher rate of smoking than those in the general population, one could hypothesize that genes associated with smoking might be overrepresented in schizophrenia and thus help explain their increased smoking incidence. Although a number of genes have been proposed to explain the increased smoking risk in schizophrenia, none of them have been consistently linked to smoking and schizophrenia, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 43 publications
6
35
0
Order By: Relevance
“…56,57 Interestingly, nAChR genes, which have been previously associated with smoking addiction, may confer risk for schizophrenia. 58 Cognitive processes that are often reported to be impaired in patients with schizophrenia, such as attention and working memory, have been implicated in research on cortical thinning in patients with severe mental illness [59][60][61] as well as in research on the effects of smoking on brain microstructure. 43,44 Furthermore, these cognitive processes are modulated by the cholinergic system, 62 and there may be lower nAChR availability in several brain regions in individuals with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…56,57 Interestingly, nAChR genes, which have been previously associated with smoking addiction, may confer risk for schizophrenia. 58 Cognitive processes that are often reported to be impaired in patients with schizophrenia, such as attention and working memory, have been implicated in research on cortical thinning in patients with severe mental illness [59][60][61] as well as in research on the effects of smoking on brain microstructure. 43,44 Furthermore, these cognitive processes are modulated by the cholinergic system, 62 and there may be lower nAChR availability in several brain regions in individuals with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is no published study investigating the pharmacogenetic interaction of a cholinergic polymorphism with nicotine on neurocognition in schizophrenia. So far, there is only one published study providing direct molecular genetic evidence for the smokingschizophrenia comorbidity (Hong et al 2011b). That study revealed that the CHRNA5 SNP rs16969968 (Asp398Asn) was simultaneously linked to smoking and schizophrenia in the same cohort (Hong et al 2011b).…”
Section: Discussionmentioning
confidence: 99%
“…So far, there is only one published study providing direct molecular genetic evidence for the smokingschizophrenia comorbidity (Hong et al 2011b). That study revealed that the CHRNA5 SNP rs16969968 (Asp398Asn) was simultaneously linked to smoking and schizophrenia in the same cohort (Hong et al 2011b). Thus, it remains to be investigated whether genetic variants within the CHRNA3/CHRNA5 gene cluster modulate the effects of nicotine on schizophrenia endophenotypes in patient samples.…”
Section: Discussionmentioning
confidence: 99%
“…For example, variants in nAChR genes have been associated not only with smoking quantity and nicotine dependence, but also with alcohol and cocaine dependence [35]. Detected associations between schizophrenia and variants in CHRNA3 [44], CHRNA5 [45], and CHRNA7 [46] suggest a function for nAChRs in schizophrenia predisposition. In a recent GWAS combining five psychiatric disorders (schizophrenia, bipolar disorder, major depressive disorder, autism spectrum disorders, and attention deficit hyperactivity disorder), two calcium channel subunits, CACNA1C and CACNB2 , were identified [47].…”
Section: Neuregulin Signaling Pathwaymentioning
confidence: 99%